Pendampingan Kegiatan Belajar di Rumah Melalui Media Pembelajaran Inovatif di Masa Pandemi COVID-19 - Siti Fatimah; Budiono; Umi Mahmudah; Khaerus Syahidi (BALE LITERASI, 2021)
Learning From Home (LFH) is the best solution during the COVID-19 pandemic. LFH is a challenge for teachers, especially in preparing materials, determining methods, and making appropriate learning media. For children with special needs, LFR is a new experience that is not easy to implement. The aims of this community service were: 1) to overcome problems and help the community, especially children with special needs who get obstacles in learning activities at home; 2) create interesting learning media for studying at home; and 3) evaluation. This service was carried out in May 2021 for three days with 3 children with special needs. The media created are science and mathematics media made from used goods such as making puzzles and toy phones. The results of this service were the help of online learning at home during COVID-19 pandemic for children with special needs, the existence of interesting learning media so that learning at home becomes fun, and the increased knowledge and motivation of learning for children with special needs after using learning media.